Chemical Constituents and Biological Activities of Flavonoids From Hydroponically Grown Pegaga (Centella Asiatica, Linn.,Urban) Extracts - Othman, Fezah (2003)
This study was carried out mainly to determine the major flavonoid compounds present in Centella asiaticae extracts and their allelopathic, anti-microbial and anti-inflammatory activities. The yield of extracts of C. asiatica was also determined and it was found that methanol was the most effective solvent to obtain crude extract from C. asiatica. Analysis on the nutrient composition of C. asiatica showed that the mean values of the nutrients analysed were about the same among the four groups (leaf, petiole including stolon, root and whole plant). The mineral profiles showed that C. asiatica leaf contains significantly (p<0.05) higher levels of P, Fe, Na and Mg compared to other parts; Ca and K contents were significantly (p<0.05) higher in the root part compared to other parts of C. asiatica. The level of vitamin C also was found significantly (p<0.05) higher in the leaf part compared to petiole including stolon, root and whole plant of C. asiatica.